Towards reconciling population nutrition goals and investment policy in Thailand: understanding how investment policy actors defined, framed and prioritised nutrition - Sirinya Phulkerd; Ashley Schram; Jeff Collin; Anne-Marie Thow; Yandisa Ngqangashe; Carmen Huckel Schneider; Sharon Friel (BMC, 2022)
Abstract Background Government's investment policy is an important driver of food system activities, which in turn influence consumers practices, dietary consumption patterns and nutrition-related health of populations. While governments globally have committed to developing coherent public policies to advance population nutrition, the objectives of investment policies are seen as being divorced from nutrition and health goals. This study aimed to examine investment policy in Thailand and explore how key actors variously define and frame their objectives in food investment policy, how nutrition issues are represented by the actors, and what discursive effects of the nutrition results were represented within the field of investment in Thailand. Methods This study conducted semi-structured interviews with 16 actors (from 23 recruited actors) from government, civil society, academia and industry. A coding framework was developed based on Bacchi's analytical framework encapsulated in the question "What's the problem represented to be?" which examines the problem and assumptions underlying a policy. Data coding was first undertaken by a lead researcher and then double-coded and cross-checked by research team. Disagreements were resolved with discussion until consensus was achieved. The interview data were analysed using thematic analysis. Results The principal "problem" represented in food investment policy in Thailand was the perceived irrelevance of nutrition to governmental commitments towards increasing productivity and economic growth. Technological innovation in food production and processing such as ultra-processed foods was perceived as a key driver of economic growth. The key assumption underlying this representation was the primacy of a "productivist" policy paradigm, via which the government focuses on industrially driven food and agriculture and expansion to increase productivity and economic growth. This entails that the nutrition needs of Thai people are silenced and remain unacknowledged in investment policy contexts, and also does not take cognisance of the term "nutrition" and its importance to economic growth. Conclusion The findings show that nutrition was not perceived as a political priority for the government and other investment actors. Promoting productivity and economic growth were clearly positioned as the primary purposes of investment within the dominant discourse. Nutrition regulation, particularly of UPF, may conflict with current investment policy directions which prioritise development of modern food production and processing. The study suggests that comprehensive policy communication about nutrition and food classification is needed.